High charge of cerebroid nests in nodular melanomas predicts tumor aggressiveness and high mutational tumoral burden: a pilot study - Caramaschi, Stefania; Mangogna, Alessandro; Bertoni, Laura; Manfredini, Marco; Farnetani, Francesca; Parente, Paola; Attino, Vito; Cazzato, Gerardo; Salviato, Tiziana; Pellacani, Giovanni; Reggiani Bonetti, Luca (Frontiers in Oncology, 2024)
Purpose: Even today, melanoma is a highly aggressive neoplasm with a high mortality rate. The nodular type is very aggressive and has cerebroid nests of melanocytes (CNMs) at the growth edge, morphologically similar to the poorly differentiated neoplastic epithelial cell clusters described in colorectal, breast, and endometrioid endometrial cancers.We selected 25 nodular melanomas (NMs) with known molecular profiles, of which the entire paraffin-embedded lesion was available. We counted CNMs under a microscopic at a magnification of 20x (i.e., a microscopic field with a major axis of 1 mm). Based on the number of CNMs in the area, melanomas were classified into three groups: G1 (CNMs ranging from 0 to 4), G2 (CNMs ranging from 5 to 9), and G3 (CNMs ≥ 10). The presence of CNMs and their counts were compared with molecular and histopathological data.Results: Seventeen (NMs) were grouped as G1 (68%), 5 as G2 (20%), and 3 as G3 (12%) based on CNMs count. The presence of CNMs correlated with epithelioid cell morphology (p < 0.05), Clark IV and V levels (p < 0.05), vascular invasion (p < 0.05), and biological mutants (p < 0.05). Melanomas with ≥ 10 CNMs more frequently show ulceration (p < 0.02) and the BRAF V600E mutation (p < 0.02).CNMs count has a predictive role regardless of tumor size; their association with the BRAF V600E mutation suggests their predictive significance in response to biologics. However, further investigations are needed to strengthen this hypothesis.